2013
DOI: 10.1007/s00268-013-2037-2
|View full text |Cite
|
Sign up to set email alerts
|

Metastases from Neuroendocrine Tumors to the Breast Are More Common than Previously Thought. A Diagnostic Pitfall?

Abstract: Metastases to the breast from neuroendocrine tumors may be more common than previously thought. Patients with a lesion to the breast and symptoms typical for NET may benefit from additional histopathological investigation, because NET metastases and mammary carcinoma have different immunohistochemical profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Previous study showed that the first recurrent site was distant in 78% of patients and patients with distant recurrence had a shorter postrecurrent survival than those with local recurrence (6). There are only few reports that have demonstrated breast metastases of primary lung neuroendocrine tumors (7)(8)(9)(10). Here, we report a case of a female patient who developed metachronous bilateral breast metastases of a lung neuroendocrine tumor.…”
Section: Introductionmentioning
confidence: 75%
“…Previous study showed that the first recurrent site was distant in 78% of patients and patients with distant recurrence had a shorter postrecurrent survival than those with local recurrence (6). There are only few reports that have demonstrated breast metastases of primary lung neuroendocrine tumors (7)(8)(9)(10). Here, we report a case of a female patient who developed metachronous bilateral breast metastases of a lung neuroendocrine tumor.…”
Section: Introductionmentioning
confidence: 75%
“…Breast metastases from NENs are not common, although there is an increased frequency reported over the last years. This could be the result of more NEN breast metastases being correctly diagnosed, as specialists are more conscious that these lesions can resemble primary carcinomas and modern technology imaging aids in reaching the correct diagnosis [5,18,19,51]. In particular, an increased occurrence of breast metastases from GEP NENs has been reported [58].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that histological analysis and morphological evaluation with the use of auxiliary immunohistochemical studies are important in reaching a correct diagnosis, particularly in difficult cases such as those with an unknown primary [32,36]. Morphological distinction is often difficult on both FNA and lumpectomy specimens due to several overlapping features and the reported frequency of neuroendocrine cells (-25%) in breast carcinoma [13,[64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Babu et al [ 7 ] described two cases of lung neuroendocrine carcinomas who presented with breast lumps. Finally, Crona et al [ 15 ] reported 8 women with lung neuroendocrine tumors (either carcinoids or large cell neuroendocrine tumors) that developed breast metastases several months after diagnosis in the majority of cases.…”
Section: Discussion/conclusionmentioning
confidence: 99%